2004
DOI: 10.1111/j.1349-7006.2004.tb03232.x
|View full text |Cite
|
Sign up to set email alerts
|

Late resistance to adenoviral p53‐mediated apoptosis caused by decreased expression of Coxsackie‐adenovirus receptors in human lung cancer cells

Abstract: t is well known that the p53 gene is frequently altered in a variety of human cancers, and its product plays a very important role in tumor suppression. Adenovirus-mediated wild-type p53 gene replacement is an attractive therapeutic strategy for various human cancers and clinical trials of this new therapy are currently being conducted in many countries. 1) One of the obstacles to this treatment, however, seems to be late resistance. Adenoviral entry into target cells is a multi-step process that includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…13,24,28,29 However, as many tumor cells tightly bind to each other or to normal stromal cells within tumor tissues, the preparation of single tumor cells is not easy, and therefore flow cytometry is an inadequate method for the detection of CAR expression in tumor tissues. In contrast, the preparation of single tumor cells is not necessary for the OBP-401-mediated GFP induction protocol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,24,28,29 However, as many tumor cells tightly bind to each other or to normal stromal cells within tumor tissues, the preparation of single tumor cells is not easy, and therefore flow cytometry is an inadequate method for the detection of CAR expression in tumor tissues. In contrast, the preparation of single tumor cells is not necessary for the OBP-401-mediated GFP induction protocol.…”
Section: Resultsmentioning
confidence: 99%
“…18,21,25,26 Decreased CAR expression has also been shown in tumor tissues after repeated injection of Ad-p53. 27,28 It is therefore necessary to assess the CAR expression level of target tumor tissues before and after Ad5-based cancer gene therapy and oncolytic virotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If expression of CAR on target cells could be increased, this could potentially yield improved efficacy of adenovirus-based therapies. We previously established H1299-R5 human lung cancer cell line refractory to adenovirus infection by five-time repeated infections (Tango et al, 2004). The observation that CAR expression markedly diminished as the cells are repeatedly infected with adenovirus suggests that the levels of CAR expression could be altered.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that Ad-p53 effects depended on the Ad infectivity 18,19 and were influenced by the CAR, but not by the integrins expression level. 20,21 Our data also revealed that Ad-p53-mediated cytotoxicity was linked with the CAR levels and Ad-GFP infectivity was primarily subjected to the CAR expression. The present data, however, does not rule out an association between the p53 status and Ad-p53-mediated antitumor effects as a multiple comparison test in this study revealed the positive correlation.…”
Section: Discussionmentioning
confidence: 53%